Predictive factors for mortality in patients with methicillin‐resistant Staphylococcus aureus bloodstream infection: impact on outcome of host, microorganism and therapy. (17th January 2013) - Gasch, O.; Camoez, M.; Dominguez, M. A.; Padilla, B.; Pintado, V.; Almirante, B.; Molina, J.; Lopez‐Medrano, F.; Ruiz, E.; Martinez, J. A.; Bereciartua, E.; Rodriguez‐Lopez, F.; et al.
Abstract Mortality related to methicillin‐resistant Staphylococcus aureus (MRSA) bloodstream infection (BSI) remains high, despite changes in the epidemiology. To analyze the current predictive factors for mortality we conducted a prospective study in a large cohort of patients with MRSA‐BSI from 21 Spanish hospitals. Epidemiology, clinical data, therapy and outcome were recorded. All MRSA strains were analysed, including susceptibility to antibiotics and molecular characterization. Vancomycin MICs (V‐MIC) were tested by the E‐test and microdilution methods. Time until death was the dependent variable in a Cox regression analysis. Overall, 579 episodes were included. Acquisition was nosocomial in 59% and vascular catheter was the most frequent source (38%). A dominant PFGE genotype was found in 368 (67%) isolates, which belonged to Clonal Complex (CC)5 and carried SCCmecIV and agr2. Microdilution V‐MIC50 and V‐MIC90 were 0.7 and 1.0 mg/L, respectively. Initial therapy was appropriate in 66% of episodes. Overall mortality was observed in 179 (32%) episodes. The Cox‐regression analysis identified age >70 years (HR 1.88), previous fatal disease (HR 2.16), Pitt score >1 (HR 3.45), high‐risk source (HR 1.85) and inappropriate initial treatment (HR 1.39) as independent predictive factors for mortality. CC5 and CC22 (HR 0.52 and 0.45) were associated with significantly lower mortality rates than CC8. V‐MIC ≥1.5 did not have a significant impact on mortality, regardless of the method used to assess it.